PENGARUH JENIS MEDIA KOROSIF TERHADAP LAJU KOROSI BESI COR KELABU - Windarta Windarta (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2014)
Corrosion is one of dangerous-phenomenon which can generate a lot of loss. Grey cast iron is the most useful material by a human being to various industrial need and engineering. This use is triggered from advantage its use.  The use of grey  cast iron in various area  causes grey cast iron has to deal with various environment.  This research aim to  determine corrosion rate of grey cast iron in  corrosive media of the sea, condensation of NaCl  5 % concentration, and calcify condensation in concentration 5 %. Method used by taking data from appliance echem corrosion test. Result got to be analysed by softcorr 342 DC corrosion . Result of data analysis indicated that at corrosive media type sea  smallest corrosion rate was 2,194 mpy and biggest 17,279 mpy. The smallest Corrosion rate at corrosive media  of Nacl was 2,663 mpy and biggest 5,800 mpy. While corrosion rate at corrosive media  of  calcify condensation was 0,003 until 12,992 mpy. Corrosion type  at the sea and salt condensation corrosive media was pitting corrosion.